Signs and Codes in Early Childhood: An Investigation of Young Children's Creative Approaches to Communication. Issue 2 (May 2015) - Guo, Karen; Mackenzie, Noella
PEOPLE COMMUNICATE AND MAKE meaning through the use of the signs, codes and rules of their community and its language/s. On the way to learning these signs, codes and rules, children often create or invent their own unique and sometimes temporary systems of meaning making. In this paper we use Vygotsky's concept of semiotic mediation and Bernstein's code theory to reflect on some examples of children's creative approaches to communication that involved the creation and use of signs. We will argue that young language learners' invention of their own languages and creative use of drawing as a form of sign creation are symbolic expressions of their intent to generate and reinforce desired social and cultural situations of learning. We conclude that individuals mediate social and individual functioning in order to make meaning of their world, and argue for a move away from viewing second language learning and emergent writing as static sets of abilities to a more dynamic interpretation.